Reading Guide and Gadget: How to Build Digital Literacy Through Primary Education Student Learning - Amalia, Rina Rizki; Suharto, abdul Wacid Bambang (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article aims to reconstruct reading guide learning strategies and devices as learning media to develop students' digital literacy in basic education. This is literature research. We gathered the data for this study by searching for relevant articles on the Google Scholar page. We then employ the content analysis technique to examine the collected data. The results show that the use of reading guide strategies and gadgets in learning to develop students' digital literacy in primary education is carried out through four stages, namely the introduction and preparation of WhatsApp groups, the pre-reading stage, the reading stage, and the post-reading stage. In all three stages, the teacher shares the reading link with students through the class WhatApp group, instructs them to read it using their gadgets, and asks them to respond to questions based on their reading results on the survey service within the class WhatApp. This study's limitation lies in its conceptual nature, necessitating the testing of its results through experimental research activities in primary education institutions.